Developing Human Resource Competitiveness in The Sharia Rural Bank Industry Based on Positioning Strategy - Arif Julianto Sri Nugroho; Tasari Tasari; Anna Febrianty Setianingtyas; Dandang Setyawanti; Ummu Hany Almasitoh; Rizky Windar Amelia (Annals of Human Resource Management Research, 2026)
Purpose: This study explores the competitive excellence of human resources in Islamic Rural Banks (BPR Syariah) in the Soloraya region. It aims to identify marketing strategies to enhance public trust and satisfaction with the services provided by these banks in the industry 4.0 era, addressing the "eight percent trap". Research Methodology: This study uses a quantitative multivariate multidimensional scaling test to examine the competitive excellence of human resources in Islamic banking services, focusing on regional economic competitiveness in Selangor. The study involved 400 respondents from six Islamic BPRs using purposive sampling. The variables assessed included knowledge and technology, business competition, career development, and educational cost effectiveness. This study highlights the impact of human resource performance on Islamic banking services in the industry 4.0 era. Results: A positioning map of each Sharia BPR was created based on the competitive excellence of its human resources, both qualitatively and quantitatively. Conclusions: This competitive excellence positioning map can be used to create competitive strategies for each BPRS, thereby realizing a robust banking industry model that optimally contributes to business competitiveness and the increasing economic welfare of the Sharia community in the Selangor region. Limitations: This research has limitations as the object of observation is only six BPRS in the Soloraya region through customer perceptions and human resources, so the model cannot be generalized more widely. Contributions: The findings of the model can be used as material for strategic management science studies in the competitive realm of the BPRS industry based on the positioning tests.